Three-dimensional soft tissue changes after reduction malarplasty in female patients. Issue 12 (December 2022) - Lim, H.-K.; Choi, Y.-J.; Choi, W.-C.; Song, I.-S.; Lee, U.-L.
Abstract: The aim of this study was to determine the three-dimensional soft tissue changes after reduction malarplasty. Soft tissue changes relative to the amount of movement of the zygomatic bone were studied. Pre- and postoperative cone beam computed tomography images of 21 female patients were superimposed. The anterior-most point of the body osteotomy (point A), arch osteotomy site (point D), and points dividing line A–D into thirds (points B and C) were marked on lateral view images. The vertical distances from the midsagittal line to the centre of the zygomatic bone and the outer prominence of the soft tissue were measured on the coronal view of each image. The proportion of the change in soft tissue to that of the bone before and after surgery was calculated for each point. The relationship between body mass index and the soft tissue change ratio, and the differences in soft tissue changes at each point were analysed. Mean soft tissue changes for points A, B, C, and D were 53.43%, 66.66%, 63.67%, and 57.23%, respectively. The amount of soft tissue change at point B was greater than that at points A and D, which were osteotomy sites. There was no statistical correlation between body mass index and the soft tissue change ratio at each point.